Present Status of Aquaculture and Socio-Economic Condition of Fish Farmers in a Rural Setting in Bangladesh (Research in Agriculture Livestock and Fisheries, 2020)
The socio-economic condition of fish farmers was assessed in the HabiganjSadarupazila, Habiganj, Bangladesh to determine the constraints and vulnerability of thecommunity in term of aquaculture. Data from 30 fish farmers were collected duringJanuary to May 2019. Among surveyed farmers, most of the pond size (37.61%)ranged between 0.02 ha to 0.06 ha and 63.33% of ponds under single ownership. Mostof the farmers were interested to stock rohu, catla, mrigal along with other species andaverage stocking density was found to be 16236 fry/ha. All farmers provided feeds forthe cultured species and 73.33% farmers have taken measures against diseaseoutbreak. The highest production was estimated as 6.19 MT/ha/year and lowestproduction was 0.54 MT/ha/year. Highest income of farmer was reported as 5,00,000Tk/ha/year and the lowest as 74534 Tk/ha/year. Highest 34.38% farmers in the studyarea reported high cost of feed is the most important constraint. The study indicatedthat majority of fish farmers (33.33%) were in age structure of 31-40 years. Similar tothe religious profile of the population, Muslims (93.33%) dominated the ownership.Among all the farmers, 40% received primary level education. The study revealed that60% of farmers lived in joint families with tin shed house (43.33%). All farmers hadelectricity in their house and at least one mobile phone. Among the farmers 53.33%have good sanitary facility and 83.33% farmers had own tubewell for drinking waterfacility. 50% farmers received health service from village doctor and 33.33% farmersreceived technical training on fish farming.Res. Agric., Livest. Fish.7(2): 329-339,  August 2020